Intensification of expression of syntactical constructions in the Ukrainian and Russian advertising texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the author analyses some means of  intensification of expression of syntactical constructions in the Ukrainian and Russian advertising texts – a compression and a word order. The author concludes about subordination of these means of the main advertising pragmatical purpose.
Keywords: expression; advertising text; word order